Rapid predictions of the colour purity of luminescent organic molecules. Issue 12 (13th January 2022) - Ahmad, Shawana A.; Eng, Julien; Penfold, Thomas J.
Abstract : Designing luminescent organic materials exhibiting narrowband emission is crucial for achieving high resolution and energy efficient organic light emitting diodes (OLEDs), but remains a significant challenge. Abstract : Designing luminescent organic materials exhibiting narrowband emission is crucial for achieving high resolution and energy efficient organic light emitting diodes (OLEDs), but remains a significant challenge. Herein we establish the key factors determining the emission full-width at half-maximum (FWHM) of 27 organic functional molecules exhibiting emitting states of different characteristics, including π–π*, charge transfer and multiple-resonance. We demonstrate that the emission FWHM can be interpreted within the displaced harmonic oscillator model (DHO), meaning that predictions can be made using ground state frequency and excited state gradient calculations only. This eliminates the need for time consuming calculations of excited state geometries and Hessians. While formally only valid within the Condon approximation, the DHO model provides reasonable correlations for spectra exhibiting significant Herzberg–Teller effects and not only makes it possible to predict emission FWHM, but also informs on the normal modes responsible for emission band broadening. In addition, quantum chemistry and rate calculations of three multiple-resonance type thermally activated delayed fluorescence (TADF) emitters demonstrates how the importance of direct intersystem crossing (ISC) can be increased when sulphur is used within the B–N framework. Overall, this work offers new perspectives for incorporating considerations of emission FWHM into rational molecular design and high-throughput screening procedures aiming to develop high efficiency luminescent organic materials.